2021
DOI: 10.1186/s40068-020-00213-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of potato (Solanum tuberosum L.) to nitrogen and phosphorus fertilizers at Sekota and Lasta districts of Eastern Amhara, Ethiopia

Abstract: Background Production and productivity of potato in Ethiopia is far below the world average because of soil fertility problem, pest, disease, and agronomic factors. Nutrient depletion because of soil erosion is a serious problem in Ethiopian highlands. Annually, 122 kg ha−1 nitrogen, 13 kg ha−1 phosphorous and 82 kg ha−1 potasium were estimated to deplete from Ethiopia (Haileslassie et al. 2005). From the essential nutrients especially, nitrogen and phosphorus are the most important influential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This increase of plant height with N dosage was also reported in previous research (Godebo and Belay 2020;Setu and Mitiku 2020;Tolessa et al 2017). Sebnie et al (2021) indicated that an application of mineral N fertiliser increased potato plant height compared to unfertilised plots.…”
Section: Plant Growthsupporting
confidence: 88%
“…This increase of plant height with N dosage was also reported in previous research (Godebo and Belay 2020;Setu and Mitiku 2020;Tolessa et al 2017). Sebnie et al (2021) indicated that an application of mineral N fertiliser increased potato plant height compared to unfertilised plots.…”
Section: Plant Growthsupporting
confidence: 88%
“…Poor seed quality (Hirpa et al, 2010(Hirpa et al, , 2016, potato diseases such as bacterial wilt, late blight, and viruses (Gildemacher et al, 2009;Nasir, 2016), and inadequate soil fertility management (Emana and Nigussie, 2011;Schulte-Geldermann, 2013) are claimed as the main bottleneck to increase potato productivity in the country. However, different strategies have been applied to increase potato productivity in Ethiopia, including seed quality management (seed systems management and seed production) (Gildemacher et al, 2009;Hirpa et al, 2016), water efficient and scheduled irrigation systems (Gebremariam et al, 2018;Alemayehu et al, 2023;Wabela et al, 2023), soil fertility management using nitrogen and phosphorus fertilizers (Sebnie et al, 2021;Woldeselassie et al, 2021;Amare et al, 2022), weed management (Kebede et al, 2016), integrated nutrient management (organic and inorganic mineral) (Girma et al, 2017;Mohammed and Dawa, 2018;Asaye et al, 2022), integrated disease and pest management (prevent bacterial wilt and late blight fungal disease, control of vectors and their viruses) (Wassihun et al, 2019;Andaregie and Astatkie, 2020;Wubet et al, 2022), post-harvest management (Tadesse et al, 2018;Degebasa, 2020), improved marketing systems, knowledge, and information systems, and using agricultural technologies (Gildemacher et al, 2009) are also critical for increasing potato productivity.…”
Section: Potato Production In Ethiopia and Environmental Sustainabilitymentioning
confidence: 99%
“…Tolessa (2019) found that applying 207 kgN.ha À1 in rain-fed potato production can boost potato tuber yield and marketable yield by approximately 176% and 119%, respectively, compared to the unfertilized plots. Sebnie et al (2021) reported that marketable potato yield generally increases with the N rate, and a high marketable yield of 45.5 t.ha À1 can be achieved when applying 138 kgN.ha À1 . In contrast, a fieldwork study in Ethiopia recorded a marketable potato yield of 25.5 t.ha À1 with 150 kg.ha À1 .…”
Section: Yields Components Of Apical Rooted Cuttings Of Potato Grown In Mollic Andosols Under Different N and Irrigation Regimesmentioning
confidence: 99%